2021
DOI: 10.1097/rhu.0000000000001750
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Based Physical Activity Patterns and Associations With Outcomes Among Individuals With Osteoarthritis

Abstract: Background: This study examined patterns of physical activity and associations with pain, function, fatigue, and sleep disturbance among individuals with knee or hip osteoarthritis.Methods: Participants (n = 54) were enrolled in a telephone-based physical activity coaching intervention trial; all data were collected at baseline. Self-reported measures of pain and function (WOMAC [Western Ontario and McMaster Universities Osteoarthritis Index] subscales), fatigue (10-point numeric rating scale), and PROMIS (Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Our results for sedentary time are comparable to prior studies in individuals with knee OA, those awaiting total knee replacement, and similarly aged peers without OA. Specifically, our sample spent an average of 11 waking hours in sedentary behavior (approximately 70% of their day), which is within the upper range of the 54%-82% reported in previous studies for individuals with knee OA [74][75][76] and the upper range of 55%-75% reported in previous studies for similarly aged peers without OA. [77][78][79][80][81][82] Given that participants in our sample were scheduled for total knee replacement within the next month, some of the sample may have had more severe knee OA than participants in prior studies and may explain the differences observed in sedentary time, step counts, and stepping intensity.…”
Section: Siƫngsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results for sedentary time are comparable to prior studies in individuals with knee OA, those awaiting total knee replacement, and similarly aged peers without OA. Specifically, our sample spent an average of 11 waking hours in sedentary behavior (approximately 70% of their day), which is within the upper range of the 54%-82% reported in previous studies for individuals with knee OA [74][75][76] and the upper range of 55%-75% reported in previous studies for similarly aged peers without OA. [77][78][79][80][81][82] Given that participants in our sample were scheduled for total knee replacement within the next month, some of the sample may have had more severe knee OA than participants in prior studies and may explain the differences observed in sedentary time, step counts, and stepping intensity.…”
Section: Siƫngsupporting
confidence: 80%
“…[77][78][79][80][81][82] Given that participants in our sample were scheduled for total knee replacement within the next month, some of the sample may have had more severe knee OA than participants in prior studies and may explain the differences observed in sedentary time, step counts, and stepping intensity. Beauchamp et al 74 observed that sedentary time for individuals with knee OA increased over the course of the day, with the largest percentage of sedentary time occurring in the evening hours when knee pain was generally at its worst. Although our analysis did not assess temporal trends based on time of day, we identified that sedentary time was accumulated in longer bouts.…”
Section: Siƫngmentioning
confidence: 99%
“…Recent evidence suggests that SB may be related to weight [ 4 ], depression [ 5 ], pain and disability [ 6 ], and physical function [ 7 ] in adults with KOA independent of moderate-to-vigorous physical activity (PA). In addition, sleep quality is negatively correlated with SB [ 8 ]. Obesity, a strong correlate of SB, is closely associated with KOA progression, and this association is stronger in women than in men [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy older adults, total SB is positively correlated with pain but not fatigue [ 14 ]; meanwhile, total SB in KOA is not correlated with pain but with fatigue [ 8 ]. These studies indicate that outcomes related to SB may differ by the presence or absence of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it leads to a vicious cycle of reduced blood ow to the legs, weakened muscle strength, decreased bone density [44,45], and sleep disturbances, resulting in increased fatigue [46] . In addition, some studies have reported that night-time fatigue is most closely related to ST, and fatigue may be an important barrier to reducing night-time SB [47] , which may be related to the long sedentary period related to patients' screentime (watching TV, looking at mobile phones) at night. Therefore, during the clinical follow-up of elderly TKA patients, healthcare workers should also pay attention to the degree of patient fatigue and apply timely and appropriate interventions to alleviate patient fatigue, while at the same time encouraging moderate physical activities without causing or exacerbating fatigue so as to maintain patients' physical and mental health.…”
Section: Fatiguementioning
confidence: 99%